2020
DOI: 10.1186/s12887-020-02426-w
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein- and clinical symptoms-guided strategy in term neonates with early-onset sepsis reduced antibiotic use and hospital stay: a quality improvement initiative

Abstract: Background Early-onset sepsis (EOS) is a potentially life-threatening complication of birth. Clinical symptoms are often unspecific and biomarkers have low predictive values for EOS. Therefore, clinical suspicion often leads to antibiotic therapy in neonates with a negative blood culture. In the study we evaluated if a quality improvement initiative could reduce unwarranted antibiotic use in a safe way in term neonates with culture-negative sepsis. Methods The quality improvement initiative included new treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…There are different strategies to reduce neonatal antibiotic use . One of the most popular strategies in recent years is using the EOS calculator .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different strategies to reduce neonatal antibiotic use . One of the most popular strategies in recent years is using the EOS calculator .…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic exposure in early life influences the developing microbiome and may be associated with an increased risk of asthma, allergy, overweight, diabetes, and inflammatory bowel disease later in life . Moreover, neonatal antibiotic use is associated with longer hospital stay and increased health care costs . Therefore, it is paramount to reduce unwarranted antibiotic use in newborns.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that CRP and clinical symptoms guided decision-making for early onset neonatal sepsis significantly decreased the duration of antibiotic therapy and hospital stay and hence reduced healthcare cost. 24 GA cellularity correlates directly with the occurrence of clinical infection with sensitivity of 75% and specificity of 70%. CRP with GA was found to be the best combination with sensitivity of 80% and specificity of 70%.…”
Section: Discussionmentioning
confidence: 99%
“…Gyllensvärd et al published their quality improvement report from a single hospital in Sweden 4. Their unit introduced a new guideline for intravenous antibiotics to oral amoxicillin switch for culture-negative EOI in term babies.…”
Section: Searchmentioning
confidence: 99%